Parenting stress and DNA methylation among African Americans in the InterGEN Study. Issue 6 (12th March 2018) - Wright, Michelle L.; Huang, Yunfeng; Hui, Qin; Newhall, Kevin; Crusto, Cindy; Sun, Yan V.; Taylor, Jacquelyn Y.
Abstract : Introduction: General life stress has been associated with altered DNA methylation in individuals of African Ancestry, although the relationship between parenting stress and DNA methylation has not been described. The purpose of this study was to examine the relationship between maternal parenting stress and DNA methylation among African Ancestry mother-child dyads. Methods: We evaluated epigenome-wide DNA methylation relative to parenting stress in 74 mother-child dyads using linear mixed models. Results: Significant variation in maternal DNA methylation at 95 CpG sites was associated with level of parenting stress. Notably, we identified a change in DNA methylation associated with poly (ADP-ribose) polymerase-1, which plays a key role in stress signaling. We did not identify any significant variation in child DNA methylation related to maternal parenting stress. Conclusions: However, DNA methylation patterns observed in children mirrored patterns observed in their mothers. The results suggest that differential maternal DNA methylation is associated with higher levels of parenting stress.